(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2024)
The aim of the current research is to identify the level of both ego strength and occupational stress, Also, the relationship between ego strength and occupational stress is known among a sample of workers in the General Organization for Tobacco- Damascus Branch. And to reveal the differences between the mean scores of the respondents on the ego strength scale according to the variables (sex, academic qualification), and on the occupational stress scale according to the variables (sex, occupational age). For this purpose, the researcher chose a sample consisting of (136) male and female. The ego strength scale prepared by (Baron, 1953), translated and prepared into Arabic (Kavafi, 1982), and the occupational stress scale prepared by: (Faraj Abdel Qader Taha and Mr. Mustafa Ragheb) were used. The current research reached the following consequences: The presence of a medium level of ego strength, and a high level of occupational stress, There is a statistically significant negative and inverse correlation between the scores of the respondents on the ego strength scale and their scores on the occupational stress scale, There are no statistically significant differences on the ego strength scale due to the variable (sex), while there were differences on the ego strength scale attributed to the educational qualification variable, There are no statistically significant differences on the occupational stress scale due to the variables (gender, occupational age).